Reduction in young male suicide in Scotland - Stockton Diane; Stark Cameron; Henderson Rob (BMC, 2008)
Abstract Background Rates of suicide and undetermined death increased rapidly in Scotland in the 1980's and 1990's. The largest increases were in men, with a marked increase in rates in younger age groups. This was associated with an increase in hanging as a method of suicide. National suicide prevention work has identified young men as a priority group. Routinely collected national information suggested a decrease in suicide rates in younger men at the beginning of the 21st century. This study tested whether this was a significant change in trend, and whether it was associated with any change in hanging rates in young men. Methods Joinpoint regression was used to estimate annual percentage changes in age-specific rates of suicide and undetermined intent death, and to identify times when the trends changed significantly. Rates of deaths by method in 15 - 29 year old males and females were also examined to assess whether there had been any significant changes in method use in this age group. Results There was a 42% reduction in rates in 15 - 29 year old men, from 42.5/100,000 in 2000 to 24.5/100,000 in 2004. A joinpoint analysis confirmed that this was a significant change. There was also a significant change in trend in hanging in men in this age group, with a reduction in rates after 2000. No other male age group showed a significant change in trend over the period 1980 - 2004. There was a smaller reduction in suicide rates in women in the 15 - 29 year old age group, with a reduction in hanging from 2002. Conclusion There has been a reduction in suicide rates in men aged 15 - 29 years, and this is associated with a significant reduction in deaths by hanging in this age group. It is not clear whether this is related to a change in method preference, or an overall reduction in suicidal behaviour, and review of self-harm data will be required to investigate this further.